Tindak Tutur Ilokusi dalam Lirik Lagu EP “Miracles in December” Karya EXO - Jose Leandro; Keren Prasetyanti; Amanda Pniel; Jayanti Megasari (Universitas Gadjah Mada, 2022)
The communication process in a song lyrics’ story involves a speaker and a speech partner. Song lyrics are essential to reflect the message of a song. Therefore, the researcher sought to know the meaning, purpose, and context of speech in the song lyrics in the extended play (EP) entitled “Miracles in December” by EXO that consists of five songs: “Miracles in December”, “Christmas Day”, “The Star”, “My Turn to Cry”, and “The First Snow”. The researcher chose the “Miracles in December” EP as an object because this EP has elements of interesting speech acts to study in pragmatics. In this study, researchers use a theoretical approach which will focus on discussing illocutionary speech acts from Searle's theory. The method in this research is descriptive qualitative with the use of listening and note-taking techniques. The results of this study prove that in the “Miracles in December” EP there are 156 data of illocutionary speech acts consisting of 100 data of assertive, 29 data of directive, 15 data of expressive, and 12 data of declarative.